The Relationship between Organizational Citizenship Behavior, Job Satisfaction, and Occupational Stress among Midwives Working in Healthcare Centers of Mashhad, Iran, 2014 - Shahla Nourani Saadoldin; Zahra Kohansal Daghian; Habibolah Esmaily; Elaheh Hooshmand (Mashhad University of Medical Sciences, 2016)
Background & aim: Organizational citizenship behavior (OCB) is a voluntary, organizationally desirable action that is not part of the employee's formal job requirements. Job satisfaction and stress can affect mental health of midwives, and investigating the relationship between these variables can improve the quality of healthcare services. This study, therefore, was conducted to identify the relationship between OCB, occupational stress, and job satisfaction in Iranian midwives. Methods:This descriptive-correlational study was performed on 122 midwives working at healthcare centers of Mashhad, Iran, in 2014. The participants were chosen using a census approach. The tools for data collection included a demographic questionnaire, Podsakoff's OCB Questionnaire, Minnesota Satisfaction Scale, and Karasek's Job Content Questionnaire. Data analysis was carried out using Spearman and Pearson's correlation, one-way ANOVA, and student t test were by SPSS version 20. Results: The mean age of the midwives was 38.46±7.22 years. OCB had a significant direct correlation with job satisfaction (r=0.223) and a significant negative correlation with job stress (r=-0.270)(P